ROLE OF TECHNOLOGY IN IMPROVEMENT OF POLICE ACCOUNTABILITY IN RAJASTHAN - Mishra, Siddharth Shankar (International Journal of Research -GRANTHAALAYAH, 2024)
This research paper examines the role of information and communication technology (ICT) in strengthening police accountability in Rajasthan. It highlights key initiatives such as the Crime and Criminal Tracking Network and Systems (CCTNS), Digital Police services, RajCop Citizen App, and cyber helpdesks, assessing their impact on transparency, complaint mechanisms, and citizen trust. While these digital tools have created opportunities for improved monitoring and evidence-based policing, their effectiveness remains limited due to challenges such as digital illiteracy, lack of training, data security risks, and the absence of independent evaluation. The study concludes that technology, when combined with administrative reforms, data privacy safeguards, and citizen oversight, can significantly improve police accountability in Rajasthan.